Approaching the White Cube or Approximating the Streets - Kuttner, Theodore (Street Art & Urban Creativity, 2019)
The work of OSGEMEOS is used to shed light on the issues arising from the intersection between the realms of street art and high art. The paradox of displacing street art into a gallery or museum setting is discussed, with a particular focus on the transitional period for OSGEMEOS from 2005 to 2010, during which they established their position as artists spanning the gap between the street art scene and the institutional art world. In the rst section, the critical discourse surrounding three of their exhibitions within gallery settings are analyzed in this context, alongside pertinent statements made by the artists. In the second section, the focus shifts to the highest pro le commissioned work for these artists during this phase in their careers, their 2008 mural on the façade of the Tate Modern for the exhibition titled “Street Art.” The debate surrounding the limitations concerning the displacement of street art and forces of institutionalization are presented and discussed in the context of this artwork as an attempt to gain a clearer understanding of this dilemma.